O papel do fogo nas sementes de leguminosas arbóreas de cerrado e floresta - Bonani, Nathalia [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Fire is an important factor in the dynamics of various plant communities such as the savanna formations. Species from Fabaceae family are found in both forests and Cerrado areas often presenting physical dormancy that can be broken in most cases by exposure to high temperatures. Thus, this work aims to verify the role of fire in germination and resistance of legume trees, comparing species from Cerrado and forest. In all, nine species were studied, three from forest, four from Cerrado and two with occurrence in both environments. The hypothesis was that Cerrado species seeds would have a higher resistance to fire exposure and could have their dormancy broken with increasing temperatures, whereas forest species seeds would have their viability reduced when exposed to heat shocks. All species also had their seed traits (mass, shape, permeability, water content) and germination (germination and resistance to high temperatures) measured. For heat shock tests we used four treatments (control, 100°C for 1 minuto and 3 minutos and 200°C for 1 minute) with 5 replicates each (20 seeds/treatment/species). After the treatments, the seeds were placed in germination chambers for 30 days at 27°C with photoperiod of 12 hours and germination counting performed 3 times a week. All species survived after exposure to 100°C, what seems to be important for species maintenance facing disturbance and environmental changes. In the Cerrado environment, even some small-sized seeds (Anadenanthera peregrina e Stryphnodendron obovatum) resisted the 200°C heat shock. The small size of seeds seems associated to the disturbed Cerrado system and it is not related to seed resistant to fire. Water content and seed shape had no apparently relation with the environment of occurrence. Forest species had impermeable (Schizolobium parahyba) or permeable (Anadenanthera colubrina) seeds, whereas species occurring in both environments and Cerrado had fractions of dormant and...

O fogo é um importante fator na dinâmica de várias comunidades vegetais, como é o caso das formações savânicas. Espécies da família Fabaceae estão presentes tanto em áreas florestais e de Cerrado, apresentando com frequência dormência física que pode, na maioria das vezes, ser quebrada por meio da exposição a altas temperaturas. Desta forma, o presente trabalho tem como objetivo verificar o papel do fogo na germinação e resistência de sementes de leguminosas arbóreas, comparando espécies de Cerrado e de floresta. Ao todo, foram estudadas nove espécies, sendo três de floresta, quatro de Cerrado e duas de ocorrência em ambos ambientes. As hipóteses foram de que sementes de espécies de Cerrado possuem maior resistência à exposição ao fogo, podendo ter sua dormência quebrada com o aumento de temperaturas, enquanto que sementes de espécies florestais teriam sua viabilidade reduzida quando expostas aos choques térmicos. Todas as espécies tiveram atributos de semente (peso, forma, permeabilidade, teor de água) e germinação (germinabilidade e resistência a altas temperaturas) mensurados. Para os testes de choque térmico, foram utilizados 4 tratamentos (controle; 100ºC por 1 e 3 minutos e 200ºC por um minuto) com 5 réplicas cada (20 sementes/tratamento/espécie). Após os tratamentos, as sementes foram colocadas em câmaras de germinação por 30 dias a 27ºC e fotoperíodo de 12h, realizando-se o acompanhamento da germinação três vezes por semana. Todas as espécies resistiram à exposição a 100°C 1 minuto, o que é uma característica relevante para manutenção das espécies frente a distúrbios. No ambiente de Cerrado mesmo algumas sementes consideradas pequenas (Anadenanthera peregrina e Stryphnodendron obovatum) resistiram ao choque de 200°C. O tamanho pequeno das sementes parece estar mais associado ao ambiente disturbado do Cerrado e não está relacionado à resistência das sementes ao fogo. Teor...
Keywords: Sementes; Sementes - Desenvolvimento; Fogo e ecologia; Germinação; Sementes - Viabilidade; Ecologia vegetal; Leguminosa; Cerrados; Florestas